Reaching hard-to-reach people through digital means : Citizens as initiators of co-creation in public services - Jalonen, Harri; Kokkola, Jussi; Laihonen, Harri; Kirjavainen, Hanna; Kaartemo, Valtteri; Vähämaa, Miika (Emerald, 2021)
Purpose This paper considers the potential of social media for developing public services. The paper approaches social media as a context that can provide information that might otherwise be unattainable. The focus of analysis is on a special hard-to-reach group of marginalized youths who appear to have isolated themselves from society. Design/methodology/approach The authors answer the question: How can the experiences of socially withdrawn youth as shared on social media be used to enrich the knowledge base relating to the initiation phase of co-creation of public services? The data retrieved from the Finnish discussion forum are analyzed using the combination of unsupervised machine learning and discourse analysis. Findings The paper contributes by outlining a method that can be applied to identify expertise-by-experience from digital stories shared by marginalized youths. To overcome the challenges of making socially withdrawn youths real contributors to the co-creation of public services, this paper suggests several theoretical and managerial implications. Originality/value Co-creation assumes an interactive and dynamic relationship where value is created at the nexus of interaction. However, the evidence base for successful co-creation, particularly with digital technology, is limited. This paper fills the gap by providing findings from a case study that investigated how social media discussions can be a stimulus to enrich the knowledge base of the co-creation of public services.
Keywords: Co-creation; Public service organization; Socially withdrawn youths; Digitalization; social media; fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|